Berczeli Anzelm Károlyhoz - Oravsky Dionyz (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1974)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek